FTIR–ATR spectroscopy applied to quality control of grape-derived spirits - Anjos, O. (2017)
The Fourier transform infrared (FTIR) spectroscopic method with attenuated total reflectance (ATR) was used for predicting the alcoholic strength, the methanol, acetaldehyde and fusel alcohols content of grape-derived spirits. FTIR-ATR spectrum in the mid-IR region (4000-400 cm(-1)) was used for the quantitative estimation by applying partial least square (PLS) regression models and the results were correlated with those obtained from reference methods. In the developed method, a cross-validation with 50% of the samples was used for PLS analysis along with a validation test set with 50% of the remaining samples. Good correlation models with a great accuracy were obtained for methanol (r(2)=99.4; RPD=12.8), alcoholic strength (r(2)=97.2; RPD=6.0), acetaldehyde (r(2)=98.2; RPD=7.5) and fusel alcohols (r(2) from 97.4 to 94.1; RPD from 6.2 to 4.1). These results corroborate the hypothesis that FTIR-ATR is a useful technique for the quality control of grape-derived spirits, whose practical application may improve the efficiency and quickness of the current laboratory analysis.